Improved Forward Backward Method With Spectral Acceleration for Scattering From Randomly Rough Lossy Surfaces - Brennan, Conor; Dung Trinh-Xuan; Mullen, Marie; Bradley, Patrick; Condon, Marissa (IEEE transactions on antennas and propagation, 2013)
An efficient and accurate iterative method is proposed for computing electromagnetic (EM) scattering from 1-D dielectric rough surfaces. The communication improves the convergence of forward backward method, applying it to the problem of 2D wave scattering from random lossy rough surfaces using a coupled surface integral equation formulation. A matrix splitting technique is introduced to reduce the number of matrix-vector multiplications required by the correction step and Spectral Acceleration (SA) is applied to reduce the computational complexity of each matrix-vector product from O(N 2 ) to O(N). The proposed method is called the improved forward backward method with spectral acceleration (IFBM-SA). The numerical analysis demonstrates that IFBM-SA has a higher convergence rate than FBM-SA and a recent technique which is used as a reference method. Moreover, IFBM-SA is more robust than the reference method and has smaller storage requirements meaning that it can readily scale to larger problems. In addition an eigenvalue based analysis is provided illustrating how the improvement step works.